Heterogeneity and plasticity of tissue-resident memory T cells in skin diseases and homeostasis: a review - Liu, Guomu; Wang, Ziyue; Li, Shanshan (Frontiers in Immunology, 2024)
Skin tissue-resident memory T (Trm) cells are produced by antigenic stimulation and remain in the skin for a long time without entering the peripheral circulation. In the healthy state Trm cells can play a patrolling and surveillance role, but in the disease state Trm cells differentiate into various phenotypes associated with different diseases, exhibit different localizations, and consequently have local protective or pathogenic roles, such as disease recurrence in vitiligo and maintenance of immune homeostasis in melanoma. The most common surface marker of Trm cells is CD69/CD103. However, the plasticity of tissue-resident memory T cells after colonization remains somewhat uncertain. This ambiguity is largely due to the variation in the functionality and ultimate destination of Trm cells produced from memory cells differentiated from diverse precursors. Notably, the presence of Trm cells is not stationary across numerous non-lymphoid tissues, most notably in the skin. These cells may reenter the blood and distant tissue sites during the recall response, revealing the recycling and migration potential of the Trm cell progeny. This review focuses on the origin and function of skin Trm cells, and provides new insights into the role of skin Trm cells in the treatment of autoimmune skin diseases, infectious skin diseases, and tumors.